2017
DOI: 10.21873/anticanres.12170
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors and a Survival Score for Patients Irradiated for Metastatic Spinal Cord Compression from Carcinoma of the Salivary Glands

Abstract: Characteristics predicting outcomes identified in this study and the new survival score can guide physicians when making treatment decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In recent years, our study group has demonstrated a significant effect of RT on stabilization of initially unstable spinal bone lesions for several histologies [ 25 , 26 , 27 ]. To date, only a few small studies and case reports have measured radiotherapeutic effects on SBM of HNC patients in terms of pain control and improvements of neurologic deficits from spinal cord compression, and to the best of our knowledge, there are no existing data concerning the impact of RT on the stability of SBM from metastatic HNC [ 17 , 28 , 29 ]. Therefore, this retrospective study aimed to assess pre- and post-RT stability of affected vertebral bodies, fracture rates, and survival, and to establish potential predictive factors for stability and survival in patients with metastatic HNC.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, our study group has demonstrated a significant effect of RT on stabilization of initially unstable spinal bone lesions for several histologies [ 25 , 26 , 27 ]. To date, only a few small studies and case reports have measured radiotherapeutic effects on SBM of HNC patients in terms of pain control and improvements of neurologic deficits from spinal cord compression, and to the best of our knowledge, there are no existing data concerning the impact of RT on the stability of SBM from metastatic HNC [ 17 , 28 , 29 ]. Therefore, this retrospective study aimed to assess pre- and post-RT stability of affected vertebral bodies, fracture rates, and survival, and to establish potential predictive factors for stability and survival in patients with metastatic HNC.…”
Section: Introductionmentioning
confidence: 99%